(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
This article focuses on the cases where the politicization of the religious factor causes financial freedom in the activities of a number of informal streams and directions. Currently, there is an opinion about putting an end to this activity, holding the financing of the extremist activities to account on a legal basis.